Pengaruh Ukuran Perusahaan dan Leverage Terhadap Intellectual Capital - Bagas Saputra; Dirvi Surya Abbas; Daniel Rahandri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study was to determine the effect of company size and leverage on intellectual capital in manufacturing companies in the food and beverage sub-sector. The research time period used is the 2015-2019 period. The population of this study includes all Food and Beverage Sub-Sector Manufacturing companies listed on the BEI for the 2015-2019 period. The sampling technique was using purposive sampling technique. Based on the predetermined criteria, 10 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data logical regression analysis. The simultaneous research results show that company size and leverage have an effect on intellectual capital. The results of the research partially show that leverage has a significant positive effect on intellectual capital and company size do not have a significant effect on intellectual capital.